Urchin-like MnO2 capped ZnO nanorods as high-rate and high-stability pseudocapacitor electrodes. (20th December 2015) - Li, Wenyao; He, Guanjie; Shao, Jiajia; Liu, Qian; Xu, Kaibing; Hu, Junqing; Parkin, Ivan P.
Graphical abstract: Urchin-like ZnO@MnO2 core@shell nanostructures were synthesized and showed an improved electrochemical properties i.e. ∼59.4% retention of its initial capacitance even when current density increased 50 times and 111.3% of its original capacitance even after 5000 long-term cycles. Abstract: Urchin-like ZnO@MnO2 core@shell nanostructures were synthesized via two step easy-controlled hydrothermal methods intercalated with a carbonization process. As a powder electrode, it showed improved electrochemical properties (∼59.4% retention of its initial capacitance even when current density increased 50 times and 111.3% of its original capacitance after 5000 long-term cycles) compared with bare MnO2 nanoflakes and many reported binder-free ZnO@MnO2 electrodes, which could be considered as high-rate and high-stability pseudocapacitor electrodes.